2016
DOI: 10.1186/s12864-016-2557-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of Klebsiella pneumoniae defines signatures for planktonic, sessile and biofilm-dispersed cells

Abstract: BackgroundSurface-associated communities of bacteria, known as biofilms, play a critical role in the persistence and dissemination of bacteria in various environments. Biofilm development is a sequential dynamic process from an initial bacterial adhesion to a three-dimensional structure formation, and a subsequent bacterial dispersion. Transitions between these different modes of growth are governed by complex and partially known molecular pathways.ResultsUsing RNA-seq technology, our work provided an exhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 54 publications
1
53
0
2
Order By: Relevance
“…This result kept our attention since prophages activation was reported in other microorganism as an inducer of cell death inside microcolonies leading to biofilm dispersion [34]. Nevertheless, a direct link could not be drawn as several unique prophages and prophage-like elements were also found for the best biofilm assemblers Kp703 and Kp45.…”
Section: Discussionmentioning
confidence: 94%
“…This result kept our attention since prophages activation was reported in other microorganism as an inducer of cell death inside microcolonies leading to biofilm dispersion [34]. Nevertheless, a direct link could not be drawn as several unique prophages and prophage-like elements were also found for the best biofilm assemblers Kp703 and Kp45.…”
Section: Discussionmentioning
confidence: 94%
“…A). In this study, dispersed bacteria overexpressed a large proportion of genes involved in translation compared with the planktonic and sessile states (Guilhen et al ., ), suggesting that biofilm‐dispersed bacteria are metabolically more active. This was also demonstrated by enzymatic measurements of ATP and lactate production in S. pneumoniae , which showed that the metabolism of dispersed cells is increased compared with that in biofilm and planktonic lifestyles (Pettigrew et al ., ) (Fig.…”
Section: The Dual‐role Of the Dispersal Process In Virulencementioning
confidence: 92%
“…A. Biofilm development is a sequential process involving adhesion of cells to a surface, formation of microcolonies and biofilm maturation with the emergence of three‐dimensional structures, from which bacteria can disperse and colonize new environments. The planktonic (gray bacteria), sessile (green bacteria) and dispersed (red bacteria) states have unique transcriptional patterns (Guilhen et al ., ). B.…”
Section: Molecular Mechanisms Governing Biofilm Dispersalmentioning
confidence: 97%
See 2 more Smart Citations